ANALISIS STABILITAS EMAS SEBAGAI NILAI TUKAR DAN PENGARUH VARIABEL MAKRO EKONOMI TERHADAP PERGERAKAN HARGA EMAS DUNIA - , Syamsul Ma'arif ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Gold as a exchange rate, store of value and safe haven has been used since ancient times, even as a standard economy system. The use of gold as a standard of economic systems based on the fact that the value of gold does not depend on any party warranties, because gold has intrinsic value and is accepted by the whole world. Various studies indicate that the gold is a stable medium of exchange, a good alternative of asset diversification and safe haven. Nevertheless, gold has also been experienced depreciation as a medium of exchange caused by the discovery and exploitation of new gold mines. This study analyzed the stability of gold as a medium of exchange between 2001 to 2012 period. Election period is based on the application of the monetary system called Quantitative Easing, which fluctuations affect prices of gold, oil, and palm oil. Influence of macroeconomic variables, such as inflation (CPI-AU), interest rates (Fed funds rate) and the growth of the American economy in a changing ratio represented gross domestic product ( GDP U.S. ) were also analyzed in this research. The selection of macroeconomic variables is because the U.S. economy is one of the largest economies in the world that is expected to affect the world price of gold. Analysis that used to calculate the stability of gold is the analysis of One - Way ANOVA. This analysis uses monthly data from as many as 139 data. Results of this analysis showed that gold has a stable value as a medium of exchange for petroleum and palm oil commodities during the study period . Analysis of the influence of macroeconomic variables to movements of gold price is done with Granger causality test and VAR modeling. This test uses quarterly data as much as 47 data. Results of the Granger causality test is that the price of gold is influenced by the American GDP, while the other variables do not have statistically significant effect on the price of gold. In addition, the price of gold also influences the change in inflation in the U.S. economy .